A DESCRIPTIVE STUDY ON THE STUDENTS' ABILITY IN WRITINGRECOUNT TEXT AT THE SECOND YEAR OF SMP NEGERI 2 SRAGENIN 2009/2010 ACADEMIC YEAR - WALIYYANI, OKTONA (2010)
The research is a descriptive research. The subject of this research is the second year students of SMP N 2 Sragen in 2009/2010 academic year. The objective of this research are:(1) to describe the classroom activities in writing recount text at the second year of SMP N 2 Sragen in 2009/2010 academic year, (2) to describe the students' ability in writing recount text at the second year of SMP N 2 Sragen in 2009/2010 academic year, and (3) to describe the problem faced by the students in writing recount text at the second year of SMP N 2 Sragen in 2009/2010 academic year. The writer uses descriptive qualitative research. The writer gets the data of this research from event, informant, and document. An event is the activities in the classroom during the teaching writing recount text. Informants are the English teacher and the students. Documents are written materials or books related to the problem. The technique of collecting data is observation and interview of writing teaching-learning process. After analyzing data, the researcher knows that (1) the classroom activities in regular class are not good, the teacher explains about the material the students did not response that the teacher explains. In the favorite class, the classroom activities are good; the teacher explains material, the students' response about the teacher explains, (2) the students' ability in writing recount text is poor, because the students get score 29-69, (3) the problem faced by the students can be seen from the lack of vocabulary, the students misunderstood in grammar, the students difficult to write the elements of recount text, the students cannot write punctuation and spelling, and the other problem was in looking for the idea.